Pertanggungjawaban Kepala Daerah dan Upaya Pencegahan Korupsi - Rasul, Sjahruddin (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2008)
Performance monitoring in care of performance measurement system makes up an extremely important thing and constitutes unseparated part of good management cycle. Performance information as yield of the application of good performance measurement system at government agency brings in transparent accountability on public fund using by means of targets achievement of non-finance performance indicator fixed before. In this case, a good performance accountability system will relate public fund using with benefit enjoyed by society. Performance monitoring in care of performance indicators and analysis on inter-relation of the indicators mentioned above, namely economical, efficiency, effectiveness, equity, and excellency carried out continuously will be able to prevent negative desire and opportunity of government apparatus to corrupt. In other words, Performance Accountability System of Government Agency by means of its parameter, that is performance indicators, will be able to prevent authority abuse that cause corruption if carried out properly. Keywords: Good governance; Clean governance; Corruption prevention; Accountability; Regional Autonomy.